Daily patterns of feeding behavior, daily rations, and diets of juvenile pink salmon (oncorhynchus gorbuscha) in two marine bays of british columbia - Godin, J.-G.J. (Jean-Guy J.) (Canadian Journal of Fisheries and Aquatic Sciences, 1981)
Stomach analyses showed that pink salmon fry fed mainly during daylight hours in the littoral zone of Departure Bay and Hammond Bay, British Columbia, in May. Although the diurnal feeding patterns of the fish differed slightly between the two bays, maximum mean prey biomass in the fishes’ stomachs occurred near or at dusk in both bays. Daily rations consumed by Departure Bay and Hammond Bay fish were estimated to be 13.1 and 6.6% of their dry body weight, respectively. The fry consumed similar prey items in both bays, but in differing proportions. Harpacticoid copepods, copepod nauplii, and barnacle larvae comprised numerically 93.1 and 86.2% of the diets of Departure Bay and Hammond Bay fish, respectively. About 38% of the diet of Departure Bay fish and 51% of the diet of Hammond Bay fish comprised epibenthic prey, mainly harpacticoid copepods. The data provide additional support for the importance of the detritus-microbe-consumer type food chain supporting the production of pink salmon during their early period of marine residency.